Answers

2014-10-01T15:57:38+05:30
NaOH(aq) + HCl(aq) → NaCl(aq) + H2O(l) 
AgNO3(aq) + NaCl(aq) → AgCl(s) + NaNO3 (aq) In this case you have to know that AgCl is an insoluble solid 
Na2CO3 (aq) + 2HCl(aq) → 2NaCl (aq) + CO2(g) + H2O(l) In certain circumstances, you could add HCl (aq) to dry Na2CO3 and the equation would be: 
Na2CO3(s) + 2HCl(aq) → 2NaCl(aq) + CO2(g) + H2O(l) 

Mg(s) + 2HCl(aq) → MgCl2(aq) + H2(g) In this case the MgCl2 is (aq) because it remains dissolved in the water of the HCl aqueous solution.

0